2020
DOI: 10.3390/cancers12082304
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma: Etiology, Modeling, and Treatment

Abstract: Retinoblastoma is a retinal cancer that is initiated in response to biallelic loss of RB1 in almost all cases, together with other genetic/epigenetic changes culminating in the development of cancer. RB1 deficiency makes the retinoblastoma cell-of-origin extremely susceptible to cancerous transformation, and the tumor cell-of-origin appears to depend on the developmental stage and species. These are important to establish reliable preclinical models to study the disease and develop therapies. Although retinobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 171 publications
(381 reference statements)
1
59
0
8
Order By: Relevance
“…Human retinoblastoma is primarily comprised of cone-like cells and has been recognized as being associated with high or low expression of cone genes. 7 , 17 , 20 , 29 , 30 MYCN -driven retinoblastoma is in the group characterized by low expression of cone-associated genes, 7 and expression of cone-associated genes was further downregulated following MYCNOS1 depletion. This change in expression of cone genes is not a result of differential death; rather, it could result from a switch in cell fate in tumors deficient for MYCNOS1 ( Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human retinoblastoma is primarily comprised of cone-like cells and has been recognized as being associated with high or low expression of cone genes. 7 , 17 , 20 , 29 , 30 MYCN -driven retinoblastoma is in the group characterized by low expression of cone-associated genes, 7 and expression of cone-associated genes was further downregulated following MYCNOS1 depletion. This change in expression of cone genes is not a result of differential death; rather, it could result from a switch in cell fate in tumors deficient for MYCNOS1 ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Loss of a cone gene signature is suggestive of tumor progression, involving enriched expression of progenitor or neuronal genes. 29 However, it is unlikely that cells deficient for MYCNOS1 represent advanced tumor cells, because they exhibit reduced aggressive behaviors. We hypothesize that MYCNOS1 maintains the features of retinoblastoma/cone signature or “stemness” previously reported for MYCNOS2 34 and that loss of MYCNOS1 expression induces neuronal differentiation in MYCN -amplified retinoblastoma without RB1 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Primary treatments for intraocular disease include enucleation, intravenous CT (melphalan with or without topotecan and/or carboplatin) with focal therapy (laser therapy, cryotherapy), intra-arterial CT with focal therapy, and focal therapy alone when tumors are small at diagnosis [ 423 ]. The choice of treatment is based on the likelihood of tumor control, eye salvage, ultimate vision, and the status of the other eye weighed against acute and chronic consequences of treatment.…”
Section: Childhood Cancer and Second Primary Malignanciesmentioning
confidence: 99%
“…RB patients with germline RB1 mutation who received EBRT have a high risk of 50% to develop SPMs with advanced age including leiomyosarcoma, OS, melanoma, lung, and bladder cancer [ 426 ]. Currently, several molecular targets such as SKP2 (e.g., via the NEDD8-inhibitor pevonedistat), MDM2, histone deacetylases, or the TRK SYK are being discussed for the treatment of CT-resistant RB to improve cure rates while reducing treatment-related side effects [ 423 ].…”
Section: Childhood Cancer and Second Primary Malignanciesmentioning
confidence: 99%
“…Since the 1980s, the RB1 gene on the long arm of chromosome 13 (13q14) has been recognized as the RB tumor suppressor gene for the first time, and its pathogenic variant is involved in the occurrence of RB [5,6,[8][9][10]. Compelling studies [1,5,6,[11][12][13][14][15] indicated that the RB1 gene is an allele encoding retinoblastoma protein (pRB), and the lack of monitoring or inactivation of RB1 will lead to a decline in cell proliferation regulation function thus resulting in abnormal cell proliferation.…”
Section: Introductionmentioning
confidence: 99%